Effects of electronic resources on the reading interests of the 4th year high school students of La Immaculada Concepcion School in Pasig City - Belo, Blesilda D. (2001)
This is a study on the effects of electronic resources on the reading interests of the 4th year high school students of the La Immaculada Concepcion School. Sample of the study consists of 95 students, 30 of whom are male and 65 female. Almost all these students belong to the same age bracket and come from middle to upperclass families.